Monetary Policy, Regulation and Volatile Markets - John P. Calverley; Fernando Restoy; Jesper Ulriksen Thuesen; Andrea Vivoli; Sushil Wadhwani; Axel A. Weber (SUERF - The European Money and Finance Forum, 2008)
Turmoil in financial markets causes reflection. Is monetary policy conducted in the most efficient way? Are regulatory and supervisory arrangements adequate when market volatility increases and financial institutions come under stress? In the present SUERF Study, we have collected the reflections by an outstanding group of top officials, researchers and observers. The editors are proud to be able to present their joint insights to SUERF readers. The papers were presented at the 27th SUERF Colloquium in Munich in June 2008: New trends in asset management: Exploring the implications.
Keywords: 330; Financial markets; volatility; regulatory and supervisory arrangements; LATW; bubbles; monetary policy; asset prices; interest rate policy; LTCM; Basel II; MiFID; subprime; CDOs; Finanzsektor; Volatilität; Geldpolitik; Marktliquidität; Finanzkrise; Geldpolitik; Wirkungsanalyse; Welt